Identification of [4-[4-(methylsulfonyl)phenyl]-6-(trifluoromethyl)-2-pyrimidinyl] amines and ethers as potent and selective cyclooxygenase-2 inhibitors. - Swarbrick, M; Beswick, P; Gleave, R; Green, R; Bingham, S; Bountra, C; Carter, M; Chambers, L; Chessell, I; Clayton, N; Collins, S; Corfield, J; et al. (2009)
A novel series of [4-[4-(methylsulfonyl)phenyl]-6-(trifluoromethyl)-2-pyrimidine-based cyclooxygenase-2 (COX-2) inhibitors, which have a different arrangement of substituents compared to the more common 1,2-diarylheterocycle based molecules, have been discovered. For example, 2-(butyloxy)-4-[4-(methylsulfonyl)phenyl]-6-(trifluoromethyl)pyrimidine (47), a member of the 2-pyrimidinyl ether series, has been shown to be a potent and selective inhibitor with a favourable pharmacokinetic profile, high brain penetration and good efficacy in rat models of hypersensitivity.